Lesotho WEAP Manual - World Bank (World Bank, Washington, DC, 2017)
This analysis looks specifically at the need to ensure continued development of water resources within Lesotho and aims to empower stakeholders to act with more confidence by demonstrating that the implementation strategies can provide benefits to water resources management over a broad range of possible future scenarios. The analysis quantifies a range of possible future conditions to demonstrate the benefits that can be realized over a broad range of possible future outcomes. This quantification is based on a water resource decision support model developed specifically for Lesotho, using the Water Evaluation and Planning (WEAP) model which couples climate, hydrologic, and water management systems to facilitate an evaluation of the uncertainties and strategies of impacts on specified management metrics. The WEAP model was used to simulate the historic climate based on data from the national government archives and global datasets available in the public domain. These included 121 downscaled Global Climate Model (GCM) projections of future climate over two possible water demand future scenarios, for a total of 244 scenarios up to the year 2050. The analysis concludes the following: (a)Climate change has important determinants for the future, long-term sustainable macroeconomic development of Lesotho: (b)Domestic and industrial water security is highly vulnerable under historical and current climate conditions, as well as under the full range of climate future scenarios; (c) Agriculture production will remain vulnerable to inter-annual variability over the coming decades, particularly with continued reliance on rain fed agriculture; and (d) The Lesotho Highlands Water Project (LHWP) will continue to reliably meet transfers to South Africa over the coming decades unless climate conditions are about 5 percent drier or more than the historical record.